2017
DOI: 10.1002/anie.201610275
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of Amorphous Iron Oxide Clusters: A Non‐Classical Mechanism for Magnetite Formation

Abstract: Despite numerous studies on the nucleation and crystallization of iron (oxyhydr)oxides, the roles of species developing during the early stages, especially primary clusters and intermediate amorphous particles, are still poorly understood. Herein, both ligand-free and ligand-protected amorphous iron oxide (AIO) clusters (< 2 nm) were synthesized as precursors for magnetite formation. Thermal annealing can crystallize the clusters into magnetite particles, and AIO bulk phases with domains of pre-aligned cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 48 publications
0
49
0
1
Order By: Relevance
“…While our reaction conditions are significantly different from those used by organisms during biomineralization, our results demonstrate that this non‐classical pathway is a possible route for the precipitation of aragonite. The similarity of the particle attachment mechanisms observed in forming biominerals and in vitro suggests that a similar mechanism is indeed possible in biogenic systems. Further work is required to confirm this hypothesis.…”
Section: Figurementioning
confidence: 80%
“…While our reaction conditions are significantly different from those used by organisms during biomineralization, our results demonstrate that this non‐classical pathway is a possible route for the precipitation of aragonite. The similarity of the particle attachment mechanisms observed in forming biominerals and in vitro suggests that a similar mechanism is indeed possible in biogenic systems. Further work is required to confirm this hypothesis.…”
Section: Figurementioning
confidence: 80%
“…S5c). This pre-aligned clusters were deemed as direct precursors of iron crystal and the alignment was hypothesized based on the anisotropic structural features within the short-range structure of the clusters [31]. Furthermore, the crystalline nature and the surface state of the ex-situ products were investigated via XRD and FT-IR.…”
Section: Ex-situ Chemical Kinetic Process Exploration Of Fe 3 O 4 Sphmentioning
confidence: 99%
“…Furthermore, understanding of the formation mechanism is an essential prerequisite for establishing the scope of synthesis of Fe 3 O 4 spheres for broad applications. In previous studies [24][25][26][27][28][29][30][31][32], polyol has been widely employed as both solvent and reductant while either PAA or Na 3 Cit is used as stabilizer. Cheng et al [14] reported that the formation of Fe 3 O 4 spheres depended on the balance of surface tension and electrostatic repelling forces of citrate molecules on the surface of nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…However, with a suitable application of ionic and polymeric additives, amorphous particles can be colloidally stabilized, also regulating the kinetics of crystallization. For instance, the nucleation of amorphous phases in the presence of certain polymers and stabilizing shells limits particle growth and coalescence ,,. Alternatively certain small molecules and ions applied as isomorphic substituents impede the phase transformation of amorphous intermediates .…”
Section: On the Nature Of Materials Precursorsmentioning
confidence: 99%